Faktor-Faktor Yang Mempengaruhi Profitabilitas Bank Konvensional Di Indonesia - Rosiana, Noor Asfia; Pramono, Nugroho Heri (Magister Manajemen STIE Bank BPD Jateng, 2024)
This study aims to empirically examine the Capital Adequacy Ratio (CAR), Non Performing Loans (NPL), Net Interest Margin (NIM), inflation, and interest rates on the profitability of conventional commercial banks. The samples in this study were 23 conventional commercial banks listed on the Indonesia Stock Exchange in the 2018 - 2021 period. Sampling used a purposive sampling method. The type of data in this study is quantitative using secondary data. The data analysis technique used in this study is multiple linear regression analysis which was processed using Eviews 10. The results of this study indicate that the Capital Adequacy Ratio (CAR) proxy has no effect on Return On Assets (ROA), Non Performing Loans (NPL) has a negative effect on Return On Assets (ROA), Net Interest Margin (NIM) has a positive effect on Return On Assets (ROA), inflation has no effect on Return On Assets (ROA), and interest rates have no effect on Return On Assets (ROA)